Environmental value of forests of the Uchum Lake resort zone: fire damage assessment - S. K. Farber; N. S. Kuzmik; E. V. Goryaeva (Сибирский лесной журнал, 2022)
The results of external impacts on forest ecosystems, regardless of their origin, are expressed in a certain degree of degradation of the forest ecosystem and, as a rule, involve the identification of damage. The paper shows that before the impact, the cost of stands can be represented as the sum of ecosystem (ecological and resource) functions: C = СCi, where Ci is the cost of the i-th function of the n considered. The calculation is performed relative to a certain function, the cost of which is known. As such a function, the tax rate of payment for wood is used. It is also possible to calculate the relative market price of wood. The final values of the value of ecosystem functions, at the same time, will differ in proportion to the ratio of tax and market prices. After exposure, the cost of stands is determined by adjusting the cost of each ecosystem function. The difference between before and after exposure determines the amount of damage. In accordance with the intended purpose, as well as due to the difference in forest inventory indicators of the stands, estimates of the significance of ecosystem functions may radically differ. This means that the distribution of the shares of significance for each stand is individual. The sequence of identifying the cost of stand and further damage is demonstrated by the example of a section of pine-larch forest destroyed by fire on the territory of the Lake Uchum resort. It was found that before the fire, the cost of stand was 156 700 rubles/ha, after the fire it decreased to 27819 rubles/ha; damage was determined in the amount of 128881 rubles/ha.